Teachers’ ICT Adoption in South African Rural Schools: A Study of Technology Readiness and Implications for the South Africa Connect Broadband Policy - Mwapwele, Samuel Dick; Marais, Mario; Dlamini, Sifiso; Van Biljon, Judy (My University, 2019)
The South Africa Connect national broadband policy of 2013 aims to ensure that the country achieves universal internet access by 2030, thereby fostering digital skills development. This study investigates one dimension of the South Africa Connect policy objectives, by considering rural teachers’ adoption of information and communication technologies (ICTs) for teaching and learning at 24 schools. This research used baseline data from the Information and Communication Technology for Education (ICT4E) project undertaken in rural schools in seven South African provinces. The technology readiness index (TRI) was used as the theoretical lens. We found that the vast majority of the teachers surveyed were optimistic about the use of ICTs for teaching and learning, which suggests teachers’ readiness to use ICTs despite the existing financial, technical and digital skills challenges at their schools. We also found that the majority of the schools had policies prohibiting student use of personal digital devices, apart from calculators, on school premises. In our analysis, these policies potentially conflict with the objectives of South Africa Connect. This study contributes to theory and practice by offering empirical evidence of the usefulness of the TRI for presenting teachers’ readiness to adopt ICTs in situations of conflicting forces. The study also has the potential to contribute to policy deliberations by highlighting the possible disconnect between the schools’ bans on student personal digital devices and the objectives and targets set by the South Africa Connect policy.